2005
DOI: 10.1073/pnas.0505350102
|View full text |Cite
|
Sign up to set email alerts
|

Biofilm formation and phenotypic variation enhance predation-driven persistence of Vibrio cholerae

Abstract: Persistence of the opportunistic bacterial pathogen Vibrio cholerae in aquatic environments is the principal cause for seasonal occurrence of cholera epidemics. This causality has been explained by postulating that V. cholerae forms biofilms in association with animate and inanimate surfaces. Alternatively, it has been proposed that bacterial pathogens are an integral part of the natural microbial food web and thus their survival is constrained by protozoan predation. Here, we report that both explanations are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
288
0
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 299 publications
(297 citation statements)
references
References 49 publications
7
288
0
2
Order By: Relevance
“…Biofilm production is strongly implicated in V. cholerae disease transmission and environmental survival on biotic and abiotic surfaces (Watnick et al, 2001;Kierek and Watnick, 2003;Matz et al, 2005;Nielsen et al, 2006;Fong et al, 2010;Tamayo et al, 2010). We find that biofilms exclude immotile planktonic cells from gaining access to the interior and from remaining bound to the biofilm surface.…”
Section: Introductionmentioning
confidence: 71%
“…Biofilm production is strongly implicated in V. cholerae disease transmission and environmental survival on biotic and abiotic surfaces (Watnick et al, 2001;Kierek and Watnick, 2003;Matz et al, 2005;Nielsen et al, 2006;Fong et al, 2010;Tamayo et al, 2010). We find that biofilms exclude immotile planktonic cells from gaining access to the interior and from remaining bound to the biofilm surface.…”
Section: Introductionmentioning
confidence: 71%
“…The formation of clumps and biofilm is another common prey defence mechanism in bacteria, which is known to reduce the risk of predation by particle-feeding ciliates (e.g. Matz et al 2005;Meyer & Kassen 2007). According to our follow-up experiment, predation by T. thermophila can increase the biofilm formation of S. marcescens (V.-P. Friman, J.…”
Section: Discussionmentioning
confidence: 99%
“…Rapid evolution of prey traits can also have important correlated consequences on other species interactions. For example, predation by free-living protozoa has been suggested to increase survival of pathogenic bacteria outside their host (Matz et al 2005) and to maintain genetic diversity required for evading the host immune system ( Wildschutte et al 2004). Yet, long-term studies where both evolutionary and ecological dynamics of predator-prey interaction are considered simultaneously in different environmental conditions are rare.…”
Section: Introductionmentioning
confidence: 99%
“…Biofilm maturation could induce structural homogeneity due to the increased presence of larger building blocks (for example, algae) that shape the overall architecture (Besemer et al, 2007), and repeatedly observed sloughing may induce a certain turnover and loss of stratification of the community. In addition, protozoan grazing is known to affect bacterial growth and survival in biofilms (Matz et al, 2005) and may differentially shape community structure in the base and streamer.…”
Section: Stream Biofilm Differentiation K Besemer Et Almentioning
confidence: 99%